Implementasi Perancangan Sistem Informasi Akuntansi Penjualan BBM Berdasarkan SAK Entitas Privat (Studi Kasus Pada Unit SPBU PT Bumi Laksamana Jaya) - Jannati, Nur Hafnil; Nurhazana (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to implement the design of a fuel sales accounting information system at PT Bumi Laksamana Jaya's gas station units based on the Private Entity Financial Accounting Standards (SAK-EP). The background of this research is based on the need for PT BLJ's gas station units to improve the quality of sales transaction recording and financial reporting through a more computerized system in accordance with the latest accounting standards. The research method used is qualitative with a descriptive approach. Data collection techniques included observation, interviews, and documentation. This study discusses the interface of the accounting information system designed using the prototype method, an approach that involves the creation of a software prototype. The results indicate that, based on the prototype display, the designed sales accounting information system is feasible for implementation and use at PT BLJ's gas station units, improving operational efficiency, reducing the risk of errors, and providing accurate, timely, and digitized sales transaction recording and financial reporting. Therefore, this system is expected to contribute to helping the company improve operational performance and strengthen corporate data security to enhance transparency and accountability in financial reporting at PT BLJ's gas station units.